Efficient solar cells are more stable: the impact of polymer molecular weight on performance of organic photovoltaics. Issue 19 (20th April 2016) - Ding, Z.; Kettle, J.; Horie, M.; Chang, S. W.; Smith, G. C.; Shames, A. I.; Katz, E. A.
Abstract : The principle remaining challenge in the research area of organic photovoltaic (OPV) materials is to develop solar cells that combine high efficiency, stability and reproducibility. Abstract : The principle remaining challenge in the research area of organic photovoltaic (OPV) materials is to develop solar cells that combine high efficiency, stability and reproducibility. Here, we demonstrate an experimental strategy which has successfully addressed this challenge. We produced a number of samples of the highly efficient PTB7 polymer with various molecular weights ( M n ∼ 40–220k). OPV cells fabricated with this polymer demonstrated significant improvement of the cell efficiency (by ∼90% relative) and lifetime (by ∼300% relative) with the M n increase. We attribute these effects to the lower density of recombination centers (persistent radical defects revealed by EPR spectroscopy) and better photoactive layer morphology in the samples with higher M n . Relevance of the observed correlation between the OPV efficiency and stability is discussed.